LogP Modelling of List Algorithms - Amme, W.; Braun, P.; Löwe, W.; Zehendner, E. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1999: Anais do XI Symposium on Computer Architecture and High Performance Computing, 1999)
We present techniques for distributing lists for processing on distributed and shared memory architectures. The LogP cost model is extended for evaluating the schedules for the given problems and architectures. We consider both bounded and unbounded lists. The theoretical results are confirmed by measurements on a KSR-1.